Effect of LHRH analogs on lower urinary tract symptoms associated with advanced prostate cancer in real clinical practice: ANALUTS study. Issue 8 (7th September 2022) - Morote, Juan; Gómez‐Caamaño, Antonio; de Celis, Raúl Poza; Gómez‐Veiga, Francisco; Ciria, Juan P.; Calleja, Jesús; Extramiana, Javier; Pérez‐Sampietro, Maria; Perrot, Valerie; Angulo, Javier C.
Abstract: Aims: To estimate the prevalence of lower urinary tract symptoms (LUTS) in patients with prostate cancer scheduled to receive LHRH analogs, and to assess the effectiveness of LHRH analogs on LUTS in patients presenting moderate/severe symptoms. Methods: Prospective, noninterventional, multicenter study conducted at 28 centers in Spain and Portugal. LUTS were evaluated using the International Prostate Symptom Score (IPSS) at baseline, 24 and 48 weeks after initiation of treatment. Subanalyses were performed according to age and concomitant treatment (radiotherapy, alpha‐blockers, and antiandrogens). Results: A total of 354 patients were treated with LHRH analogs for 48 weeks. The percentage of patients with moderate/severe LUTS (IPSS > 7) decreased from 60.2% ( n  = 213/354) at baseline to 52.8% ( n  = 187/354) at Week 48. Among patients with moderate/severe LUTS at baseline: 73.7% ( n  = 157/213) still had moderate/severe LUTS at Week 48; percentage reductions of patients with LUTS at Week 48 were statistically significant ( p  < 0.05) overall and by age or concomitant treatment, except for alpha‐blockers (84.2% patients receiving them still had moderate/severe LUTS at Week 48). All IPSS items, including quality of life for urinary symptoms, improved throughout the study. The only predictor of response to treatment with LHRH analogs that improved IPSS by 3 points after 48 weeks was baseline testosterone levels. Lower baseline testosterone levels were associated with greater improvement in IPSS after treatment with LHRH analogs (odds ratio 0.998, 95% confidence interval 0.996–1.000, p  = 0.0277). Conclusion: LHRH analogs have a positive effect in patients with locally advanced or metastatic prostate cancer presenting moderate/severe LUTS regardless of age or concomitant treatment received (radiotherapy, antiandrogens, or alpha‐blockers).